Spory o rolę historii w sferze publicznej na współczesnej Ukrainie - Skłokin, Wołodymyr (Kultura i Społeczeństwo, 2015)
This article discusses the debate over the social meaning of history occurring between proponents and opponents of the national paradigm in contemporary Ukrainian historiography, in the context of recent paradigmatic changes in historiography in the West. The debate centers on two competing views of the proper relation of academic history writing to politics and society. After pointing out the limitations of these two dominant perspectives, the author ends the article by discussing possible solutions, particularly John Tosh’s idea of a critical public history, which is practiced in Ukraine by Jarosław Hrycak.